Chemical Weathering and Mechanical Erosion of The Batéké Plateaus in Congo Brazzaville: Evaluation from Measurements Taken at Four Gauging Stations - Dinga, Jean Bienvenu; Petitdidier, Monique; Nganga, Dominique (European Journal of Applied Sciences, 2023)
The Batéké plateaus, in Congo Brazzaville (Republic of Congo) is part of the Congo basin, in the longitude range from14°30’East to16°30’ East and in the latitude range from 1°30’ South to 4°30’ South. Four stations were set up on the Alima, Léfini, Nkeni, and Djiri rivers, respectively. Those rivers are the main tributaries of the Congo river on its right bank. The measurements obtained at those stations permitted to study the seasonal, inter-annual variations and the annual budget of material transportation coming from those four tributaries. This work reports the results acquired during ten years of research (1998-2008) on the hydrological and hydrogeochemical plateaus Batéké in Congo Brazzaville. He aims to: to take stock of the outputs to the ecosystem of major outfalls (stations Djiri to Djiri of Mbouambé on Léfini of Gamboma on Nkéni and Tchikapika on Alima); specify the modes of transport minerals in rivers to recognize the operation of large entities upstream (rocks and forest ecosystems homogeneous) and define their contribution to the overall transport in the Congo River basin. Evaluation results indicate that mechanical erosion of 204.6 103 tons per year and a chemical alteration of 731,6 103 tons per year on all plateaus Batéké. The contributions of the entire ecosystem as a percentage in the Congo Basin are; Fluid intake: 9% of annual volume; Suspended solids: 8% of the total load, and Dissolved Solids: 7% of the total load.